Exploring English Education Students’ Teaching Practicum Experiences: A Narrative Inquiry into The Crafting of Their Teacher Identity Journey - Aminatus Sholihah (Retain: Journal of Research in English Language Teaching, 2024)
This study aims to explore the teaching practicum experiences of English Education students in shaping their teacher identity. Through a narrative inquiry approach, the author investigates the beliefs of pre-service teachers about teaching practicum and identifies the contributions of teacher education programs to their perspectives. The research also delves into the importance of teaching practicum, beliefs, and uncertainties that arise during the practicum. The findings reveal that teaching practicum experiences play a crucial role in shaping teacher identity. Through deep reflection on practicum experiences, pre-service teachers can actively construct their professional identity. These findings provide valuable insights for English Education programs and teacher training, particularly in developing teachers' competencies in pedagogy, personal, social, and professional aspects. By employing a narrative approach, this study offers a profound understanding of the transformative journey in teacher identity formation. The implications of this research can aid in the development of strong and quality teacher identities through well-planned practicum experiences.